The Influence of Executive Compensation, Independent Boards, and Liquidity on the Performance of Banking Firms Listed on the Indonesia Stock Exchange - Dellani, Dhea; Efni, Yulia; Fitri, Fitri (Strata Business Review, 2025)
Banking institutions function as financial intermediaries that rely heavily on public trust, as their operations predominantly utilize funds sourced from depositors rather than shareholders. The stability and sustainability of these institutions depend on their ability to maintain sound financial performance, which reflects managerial effectiveness in balancing liquidity adequacy, profitability, and capital sufficiency. This study investigates the influence of executive compensation, independent boards, and liquidity on firm performance measured using return on assets (ROA) among banking firms listed on the Indonesia Stock Exchange. The research employs a purposive sampling technique and analyzes 235 firm-year observations from 47 banking companies over the 2018–2022 period. Data were processed using variance-based structural equation modeling (SEM-PLS) with Warp-PLS version 5.0. The findings demonstrate that executive compensation has a significantly positive impact on firm performance. Conversely, the independent board variable shows a negative but statistically insignificant relationship with firm performance. Furthermore, liquidity exhibits a positive influence on financial performance, indicating the importance of maintaining sufficient liquid resources in supporting operational efficiency and profitability.